IMPLEMENTASI KEBIJAKAN PEMBERIAN HAK GUNA USAHA - Janri Wolden Halomoan Sirait (JIANA ( Jurnal Ilmu Administrasi Negara ), 2017)
Abstract: Policy Implementation for Giving Cultivate Right. This study aims to determinePolicy Implementation for Giving Cultivate Right the National Land Agency Regional Office ofRiau Province. This research is a descriptive study with qualitative approach. Informants in thisstudy are the people who play a role in the administration of leasehold in the Regional Office ofRiau Province National Land Agency. Data collection technique were interview, observation anddocumentation. The results of this study showed that the implementation of the policy of grantingrights to cultivate the Nasioanal Land Agency Regional Office of Riau province has not gone up,meaning that implementation is happening in the field is still not effective. Still the presence ofcompanies that do not have the right to cultivate while they have been operating.